Estrutura eletrônica da amino- e dimetilamino-benzonitrila em meio usando métodos híbridos de QM/MM - Herrera, Andrés Medina (2015)
In this research we studied the structural and electronic properties of the ground state of molecules amino-benzonitrile (ABN) and dimethylamino-benzonitrile (DMABN), isolated and in different solvents.We performed computer simulations of those molecules in different solvents as cyclohexane, dichloromethane, acetonitrile and water. The structure electronic method MP2 (second order perturbation Møller-Plesset) was used to perform quantum calculations. To study the molecules in solvent we used the hybrid sequential QM/MM method combined with the free energy gradient method. The dual fluorescence to this type of molecules is a process that has been much studied but it is not well clarified that is the cause of the process. We performed the optimization of the molecules in an isolated state and in different solvents to determine the ground state structure. In the case of the DMABN molecule the optimization was performed both at room temperature and at low temperature, near the melting point of the solvent. We studied minimum energy point and some transition states of this molecules associated with the pyramidalization or the rotation of the amino group. The results showed that the molecules are pyramidal when they are isolated, and that in polar solvent they became less pyramidal. The rotation of amino group is unfavored in both molecules, increasing this effect in polar solvents.